Graphene-based Microbial Fuel Cell Studies with Starch in sub-Himalayan Soils - Debajyoti Bose; Amarnath Bose (IAES Indonesian Section, 2017)
Microbial fuel cells with graphene based cathode and anode is the study of interest. Present work shows the capacity of sub-himalayan soil of Dehradun region of Uttarakhand, India holds potential to cater to power production from soil and organic waste matter. This can be speculated to power less energy intensive devices at the smallest level. Peak voltage of 0.69 V and current density datas are reported.Renewable energy utilization with such samples represents a sustainable usage. The soil bacterias are capable to metabolize the metal substances in the soil through symbiosis. Electric bacteria create conductive pili called nanowires enabling them to transfer electron and this can be utilized effectively.Direct electron transfer mechanisms have been investigated for this work. The biofilm developed by soil bacterias represent the central idea in making value from waste matter.